Pemanfaatan Aplikasi Trello untuk Efisiensi Agenda Manajemen Sekolah di SMK Negeri 5 Balikpapan - Natavia, Dini Sakti; Warman, Warman; Widyatmike, Widyatmike; Hasanah, Arini (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2025)
This research analyzes the use of the Trello application in improving school management efficiency at SMK Negeri 5 Balikpapan through a qualitative descriptive approach based on case studies. This research uses a qualitative descriptive approach based on case studies at SMK Negeri 5 Balikpapan, with data collection through observation, interviews and documentation. Research results show that Trello significantly improves schedule management, task distribution, and team collaboration through progress visualization, automatic reminders, and comments features. Time efficiency increases by up to 40%, while the on-time task completion rate reaches 85%. These findings support the theories of time management, Agile, and work motivation, and show that Trello has the potential to be an effective digital solution in educational management, especially in overcoming challenges related to organizing tasks and communication between team members. These findings support the theories of time management, Agile, and work motivation, and show the potential of Trello as a digital solution in educational management. It is estimated that the use of applications such as Trello can be further optimized by training staff and developing more specific features according to managerial needs in educational institutions.